2021
DOI: 10.3390/pathogens10091126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vesicular Stomatitis Virus Indiana from Insects Collected during the 2020 Outbreak in Kansas, USA

Abstract: Vesicular stomatitis (VS) is a reportable viral disease which affects horses, cattle, and pigs in the Americas. Outbreaks of vesicular stomatitis virus New Jersey serotype (VSV-NJ) in the United States typically occur on a 5–10-year cycle, usually affecting western and southwestern states. In 2019–2020, an outbreak of VSV Indiana serotype (VSV-IN) extended eastward into the states of Kansas and Missouri for the first time in several decades, leading to 101 confirmed premises in Kansas and 37 confirmed premises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…To our knowledge, we are making the first report of VSV detected in Simulium collected in habitats outside of farms and ranches with concurrent or historical epizootics of the virus. Additionally, this is the first detection of VSIV in Simulium in NM; we note that VSIV was also detected in 2020 from S. meridionale collected on a VSIV-confirmed premise in Kansas [20]. VSNJV has previously been detected in S. vittatum and S. bivittatum during outbreaks [17,21].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…To our knowledge, we are making the first report of VSV detected in Simulium collected in habitats outside of farms and ranches with concurrent or historical epizootics of the virus. Additionally, this is the first detection of VSIV in Simulium in NM; we note that VSIV was also detected in 2020 from S. meridionale collected on a VSIV-confirmed premise in Kansas [20]. VSNJV has previously been detected in S. vittatum and S. bivittatum during outbreaks [17,21].…”
Section: Discussionmentioning
confidence: 51%
“…Multiple methods for detecting virus or viral genome have been used to identify vectors potentially involved in the VSV transmission cycle. These methods have detected VSV or its genome in hematophagous dipterans including Simuliidae (black flies) [17][18][19][20][21], Psychodidae (sand flies) [22], Ceratopogonidae (biting midges) [20,23], and Culicidae (mosquito) vectors [24]; as well as non-hematophagus dipterans including houseflies, (Muscidae), root-maggot flies (Anthomyiidae), and eye gnats (Chloropidae) [17,19]. The majority of VSV detections in insects have occurred on farms and ranches during concurrent VSV outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Elucidation of natural VSV cycles is difficult due to the sporadic nature of outbreaks, and numerous insect species have been implicated in both mechanical and biological transmission [7]. VSV has been detected in field-collected C. sonorensis from past US outbreaks, including the 2019-2020 outbreak, which affected animals in states from Arkansas to Arizona [19]. Interestingly, there is evidence that VSV may be transmitted transovarially [20] and/or venereally [21] between midges, which has not been shown in Orbiviruses.…”
Section: Culicoides Sonorensismentioning
confidence: 99%
“…Tabachnick [12] refers to some of his unpublished data on infection rates in field-collected C. variipennis from New York, New Jersey, and Maryland, and C. occidentalis from California, where they found low (< 3%) minimum BTV infection rates. More recently, McGregor et al [19] reported a single VSV + pool of C. variipennis collected in Kansas during the 2020 outbreak. To date, no laboratory infection experiments using C. variipennis have been conducted, so the true vector competence of this species for any of the Culicoides-transmitted arboviruses is unknown.…”
Section: Other Putative Livestock-associated Vectorsmentioning
confidence: 99%
See 1 more Smart Citation